Income distribution of the population of Ukraine: empirical analysis using lognormal function - Мороз, Катерина Вікторівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The main focus of this article is to analyze the income distribution function of the population of Ukraine which assigns the share of the population with a per capita income to each level of income that does not exceed this level. The article, in particular, empirically tests the hypothesis about a log-normal distribution of the population of Ukraine by the level of per capita income. There were analyzed the studies dealing with this issue. We selected statistical data of the distribution of the population of Ukraine by the level of per capita equivalent income in 2007-2015 years as the main indicator of well-being.First, we analyze the dynamics of the main characteristics of the distribution of per capita income: the mode, median and the mathematical expectation, detect trends, make conclusions regarding their parity. Then, using the data of the average per capita income and on the basis of the evaluated common income parameters of lognormal distribution are calculated. Then, on the basis of parameters evaluation, the distribution of the population of Ukraine at the level of income is approximated empirically. The conclusion about the quality of the received model data is made using the Kolmogorov-Smirnov χ2- test statistics. To forecast the average and modal per capita income in 2016 their line trends are built, and then the distribution parameters are calculated for 2016. Then we use the two-parameter log-normal distribution model for short-term forecasting of the distribution of population by income. The conclusions regarding the predicted changes in average per capita equivalent income as compared with 2015 are made.